APPLICATIONS OF THE IMPACT II HIGH RESOLUTION QUADRUPOLE TIME-OF-FLIGHT (QTOF) INSTRUMENT FOR SHOTGUN PROTEOMICS - Kulyyassov , A.T.; Ramankulov , Ye.M. (Eurasian Journal of Applied Biotechnology, 2018)
Mass spectrometry is a central analytical method for protein research and other biomolecules which also demonstrated capability to detect peptides and proteins in a specific manner. Combined with appropriate sample preparation and/or enrichment, sensitivity is high enough to quantify peptides and proteins. In particular, the detection of iso-forms and different post-translational modifications is of highest interest for clinical applications, including discovery of novel biomarkers for early detection and targeted therapy of cancer and cardiovascular disease. The need to identify, characterize, and quantify proteins at ever increasing sensitivities and in even more complex samples has resulted in the evolution and development of a wide range of new mass spectrometry-based analytical platforms and experimental strategies. Among them, hybrid quadrupole time-of-flight (QToF) mass spectrometers are standard instruments in proteomic laboratories. Here, we discuss the basic concepts of mass spectrometry including performance characteristics, components of tandem mass spectrometer such as quadrupoles, ion traps, ToF mass analyzers, shotgun proteomics methods and bioinformatics analysis. The recent introduction of QToF Impact II Bruker mass spectrometer offers unrivaled mass accuracy (better than 1.45 ppm), high resolving power (40000 at m/z 1222) and a high dynamic range (1.7×105), without the need for a superconducting magnet and its associated maintenance requirements. A comparative analysis of basic performance characteristics of Impact II instrumentation such as resolving power, accuracy, mass range, optimal detection level and dynamic range is also presented in this review.